Review of/ Reseña de: Molins Roca, Jaci. Trobades amb 69 dones. Manresa: Parcir Edicions, 2022. 319 pp. ISBN: 978-84-18849-67-1 - Isabel Alonso-Breto (Feminismo/s)
Review of/ Reseña de: Molins Roca, Jaci. Trobades amb 69 dones. Manresa: Parcir Edicions, 2022. 319 pp. ISBN: 978-84-18849-67-1